2007
DOI: 10.1007/s00134-007-0634-y
|View full text |Cite
|
Sign up to set email alerts
|

Prospective evaluation of peripheral venous access difficulty in emergency care

Abstract: Peripheral intravenous access was achieved in 99% of the patients in out-of-hospital settings. Improved success rate was reported when attempts were performed by a nurse specialized in emergency care using a 16- or 18-G catheter in clean patients without a particular medical history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
105
5
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(123 citation statements)
references
References 17 publications
6
105
5
7
Order By: Relevance
“…So as to prevent this type of complication, attention should be drawn to the positioning of the tourniquet as distal as possible to the area of insertion of the catheter, with a view to reducing intravascular pressure (11) The children's non-alterable factors, such as age, sex and skin color, do not show contribution to PIP failure, which corroborates other studies (4,7,(12)(13) .…”
Section: Discussionsupporting
confidence: 78%
“…So as to prevent this type of complication, attention should be drawn to the positioning of the tourniquet as distal as possible to the area of insertion of the catheter, with a view to reducing intravascular pressure (11) The children's non-alterable factors, such as age, sex and skin color, do not show contribution to PIP failure, which corroborates other studies (4,7,(12)(13) .…”
Section: Discussionsupporting
confidence: 78%
“…2016; 26(6):e6321. 92% of adults (14) and in 86% of children (15). The success rate within two attempts is 95.47% in this study, which is higher than that in the reports mentioned above, meaning that 4.53% of patients require three or more attempts before success.…”
Section: Discussioncontrasting
confidence: 67%
“…Improved success rate was reported when attempts were performed by a nurse specialized in emergency care in patients without a particular medical history like chemotherapy, diabetes, or previous multiple hospitalizations. Initial teaching and regular practice significantly increased the success rate [15]. In our study, one of our participating centers solved the problem of difficulties in establishing venous access by a transmural infusion team composed of trained infusion nurses working both at the hospital and in the home situation, thus providing regular practice in inserting infusion needles.…”
Section: Discussionmentioning
confidence: 93%
“…In our study, the peripheral venous cannula had to be inserted at home by the home nurse of the infusion team. Lapostolle et al [15] reported a study on a total of 671 attempts to obtain peripheral intravenous access in 495 patients in emergency care in out-of-hospital settings. The first attempt was successful in 368 cases (74%) and unsuccessful in 127 (26%).…”
Section: Discussionmentioning
confidence: 99%